Cultivo de coca y minería ilegal en la Amazonía peruana - Manrique, Hernán (2024)
This article provides a narrative synthesis of the academic literature on coca cultivation and illegal mining in the Peruvian Amazon. Through secondary sources, it analyzes the expansion of these illicit economies into the eastern Amazon. In addition, the article presents and discusses four myths about illicit economies prevalent in public debate and the media, which prevent an understanding of the complexity behind these phenomena. The myths revolve around i) a full understanding of the extent and distribution of coca cultivation and illegal mining, ii) the existence of a direct relationship between illicit economies and violence, iii) the role of indigenous peoples in the expansion of these activities and, finally, iv) the absence or limited presence of the State in these contexts. Based on a narrative review of the literature, this article uses the findings of recent empirical evidence to question the validity of these myths. The article concludes with research conclusions and recommendations for the study of illicit economies.